In Vitro Investigation of Therapeutic Potential of Bare Magnetite (Fe3O4) Nanoparticles (<= 100 ppm) on Hepatocellular Carcinoma Cells - (:unkn) unknown (AMER SCIENTIFIC PUBLISHERS, 2020)
Significant ROS production capability of bare iron oxide nanoparticles in safe doses for healthy cells offers an interesting therapeutic window for cancer. In this context, the aim of the current study is to investigate therapeutic potential of the synthesized magnetite (Fe3O4) nanoparticles (similar to 80 nm) as attractive vehicles for biomedical applications on hepatocellular carcinoma cells (HepG2). To investigate their time (0-72 h) and dose (0-100 mu g/ml) dependent effect on physiological state (proliferation/cytotoxicity) and mitochondrial activity of the tumor cells, xCELLigence system and MTT assay were used, respectively. Both 50 and 100 mu g/ml of nanoparticle treatment induced significant (p < 0.01) increases in ROS production in HepG2 cells; however, similar to 4-day real-time cell analysis illustrated that all concentrations of the nanoparticles caused significant (p < 0.01) increases in proliferation of the tumor cells from 4 h after the treatment to the end of the analysis. While 50 and 100 mu g/ml of nanoparticles caused significant deteriorations in the mitochondrial activity of the tumor cells in the case of 24 h-(p < 0.05 and p < 0.01, respectively) and 72 h-treatment (p < 0.01); 24 h-treatment of 100 mu g/ml of nanoparticles and 72 h-treatment of 50 and 100 mu g/ml of nanoparticles caused significant increases in the mitochondrial activity of the tumor cells (p < 0.01) under static magnetic field (1.35 T). Although the synthesized magnetite nanoparticles have not therapeutic potential alone on HepG2 cells in doses safe for healthy cells, the results of the current study are illuminating for future magnetite nanoparticle-based biomedical applications and combination cancer therapy containing magnetite nanoparticles.
Keywords: Magnetite (Fe3O4) Nanoparticles; Hepatocellular Carcinoma Cells (HepG2); xCELLigence System; MTT Assay; Static Magnetic Field; IRON-OXIDE NANOPARTICLES; MTT ASSAY; TOXICITY; CANCER; CHEMOTHERAPY; DELIVERY; DRUG